Blended synchronous learning : final report. - Bower, Matt; Dalgarno, Barney; Kennedy, Gregor; Lee, Mark J. W.; Kenney, Jacqueline (Office for Learning and Teaching, 2014)
Final report of the Blended Synchronous Learning Project, that investigated how rich-media technologies could be used to unite remote and face-to-face students in the same live classes. Seven case studies of blended synchronous learning were conducted in higher education institutions around Australia.